Describing the phenotype in Rett syndrome using a population database. Issue 1 (1st January 2003) - Colvin, L; Fyfe, S; Leonard, S; Schiavello, T; Ellaway, C; de Klerk, N; Christodoulou, J; Msall, M; Leonard, H
Abstract : Background: Mutations in the MECP2 gene have been recently identified as the cause of Rett syndrome, prompting research into genotype-phenotype relations. However, despite these genetic advances there has been little descriptive epidemiology of the full range of phenotypes. Aims: To describe the variation in phenotype in Rett syndrome using four different scales, by means of a population database. Methods: Using multiple sources of ascertainment including the Australian Paediatric Surveillance Unit, the development of an Australian cohort of Rett syndrome cases born since 1976 has provided the first genetically characterised population based study of Rett syndrome. Follow up questionnaires were administered in 2000 to families and used to provide responses for items in four different severity scales. Results: A total of 199 verified cases of Rett syndrome were reported between January 1993 and July 2000; 152 families provided information for the follow up study. The mean score using the Kerr scale was 22.9 (SD 4.8) and ranged from 20.5 in those under 7 years to 24.2 in those over 17 years. The mean Percy score was 24.9 (SD 6.6) and also increased with age group from 23.0 to 26.9. The mean Pineda score was 16.3 (SD 4.5) and did not differ by age group. The mean WeeFIM was 29.0 (SD 11.9), indicating extreme dependence, and ranged from 18 to 75. Conclusion: We have expanded on the descriptive epidemiology of Rett syndrome and shown different patterns according to the severity scale selected. Although all affected children are severely functionally dependent, it is still possible to identify some variation in ability, even in children with identified MECP2 mutations.